Sensitization and Interoception as Key Neurological Concepts in Osteopathy and Other Manual Medicines - D'Alessandro, Giandomenico; Cerritelli, Francesco; Cortelli, Pietro (Frontiers in Neuroscience, 2016)
Abstract Historically, approaches used in manual medicine to explain patient reported symptoms have been focused on the so-called exteroceptive paradigm. Arguably, this mindset lacks an appropriate “reading system” able to interpret musculoskeletal disorders from a different perspective, where the properties of the nervous system are embraced into a more holistic and functional-related context. Interestingly, if the underpinning mechanisms of a given treatment scenario/effect are taking into account, the majority of research outcomes focuses on a proprioceptive/exteroceptive explanation, leaving ting aside the additional or even central role of interoception. Currently, to date, the application of theoretical knowledge acquired on the relatively recent neuroscientific concepts and evidence concerning of interoception, sensitization, touch, autonomic functions, inflammation, and pain into a clinical/research manual medicine scenario is lacking, even if theoretically, the impact on the possible etiological mechanisms and treatment effects seems to be important. Here, we propose the conceptual foundations for a new way of interpreting and reading patients’ clinical reported outcomes scenario based on interoception and sensitization. We argue that this will provide a foundation to create the ground for future research focusing on the hypotheses that manual therapies, specifically osteopathy, can intercede with sensitization states, at all levels, using interoceptive pathways.